Phytochemical Screening of Costa Rican Plants: Alkaloid Analysis II - Sáenz R., José A. (1965)
A total of 57 species of Costa Rican plants were tested for their alkaloid content in both acid and alkaline layers; 8 of the plants mentioned in the list are here reported for the first time as containing alkaloids.